Macro- and Microelement Composition, Antioxidant Activity, and Biological Effect of Cold-Pressed Edible Oils from Commercial and Amateur Companies - Jolanta Marciniuk; Beata Sadowska; Marzena Więckowska-Szakiel; Mateusz Borkowski; Jacek Zebrowski; Bronisław K. Głód; Kacper Marciniuk; Paweł Marciniuk (Molecules)
The aim of this study was to examine cold-pressed oils available on the Polish market derived from different plants and manufacturers in the context of their biological activity, including micro- and macroelements, antioxidant properties, antimicrobial activity, and selected effects on eukaryotic cells. In total, 76 oil samples of 34 selected oil types from nine Polish companies (five commercial and four amateur) were tested. The content of macro- and micronutrients was assessed using ICP-OES, the level of fatty acid unsaturation was examined using Fourier transform infrared spectroscopy (FTIR), and total antioxidant potential (TAP) was assessed using the DPPH method. The antimicrobial activity of the selected oils against Gram-positive and Gram-negative bacteria, as well as fungi, representing both pathogens and human microbiota, was tested using the broth microdilution method. The MTT reduction assay was used to exclude the cytotoxic effect of the oils on the human fibroblast line HFF-1. It has been concluded that the composition of cold-pressed oils varied significantly depending on the plant used and the manufacturer. The total content of the elements tested ranged from 172.91 mg/kg in Helianthus annuus oil to 1580.73 mg/kg in Silybum marianum oil. The iron concentration limits were exceeded in 10 oils, the copper concentration limits were exceeded in 34 oils, and the lead concentration limits were exceeded in 18 oils. At least one of these elements was exceeded in 40 oils (53% of the tested samples), which is why testing the concentration of elements should be a standard procedure for assessing the quality of cold-pressed oils. There was no statistically significant correlation between the content of any macro- and microelements and TAP. While TAP was strongly correlated with the spectral unsaturation index of the oils, this relationship can be used to develop a simple and rapid assessment of oils quality. The strongest antioxidant activity (over 90%) was observed for Nigella sativa oils. Interestingly, among all the tested oils, only these from Nigella sativa L., whatever the producer, possessed also strong antimicrobial activity. None of the tested oils showed cytotoxicity against eukaryotic cells, so the cold-pressed oils can be considered safe.